Looking at the Abolition of the State Civil Apparatus Commission After the Revision of the State Civil Apparatus Law from the Perspective of Fiqh Siyasah - Makiin, Inda Dzil Arsyi; Karini, Eti; Alamsyah, Mirah Satria (RechtIdee, 2024)
Law No. 1 of 2014 concerning ASN (State Civil Appratus) regulates the establishment of an independent institution called the State Civil Apparatus Commission (SCAC). SCAC has the authority, duties, and functions to oversee the merit system in ASN management. However, on October 31, 2023, there was a revision of the ASN Law into Law No. 2023. The revision of the ASN Law abolishes the existence of SCAC and transfers its authority, duties, and functions to other ministries/agencies. This research aims to examine the importance of the ASN supervisory agency and to understand the supervision system as well as the impact of the transfer of its authority, duties, and functions. Additionally, this research aims to examine the abolition of SCAC from the perspective of fiqh siyasah. This research is a normative legal study that uses secondary data in the form of primary legal materials and secondary legal materials. The research found that monitoring the merit system is very important, as it can affect Indonesia's ranking in the Government Effectiveness Index (GEI), helping Indonesia move from the lower-middle-income category to the upper-middle/high-income category. The research found that the authority, duties, and functions of SCAC were subsequently transferred to BKN. The supervision system remains the same, but there is an innovation regarding the digitalization of handling neutrality cases in elections. Moreover, the abolition of SCAC through the Revision of the ASN Law had very minimal participation from parties knowledgeable about strengthening SCAC. The lack of participation does not align with the deliberative principle found in the principles of fiqh siyasah.